PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASANDALAM RUMAH TANGGA (KDRT) DI WILAYAH HUKUM POLRES PIDIE - Suhaibah Suhaibah (Universitas Jabal Ghafur, 2020)
Domestic Violence or domestic violence (KDRT), in principle is one of the phenomenon of human rights violations so that this issue is covered as one form of discrimination, especially against women. Discrimination itself has been formulated in various legal instruments in Indonesia such as Law Number 7 of 1984 which is a form of ratification of the Convention on the Elimination of All Forms of Discrimination against women formulated by the United Nations (UN), and more recently is Law No. 23 Tahuo 2004 on Domestic Abolition (KDRT), but there is still no significant impact for women victims of discrimination. In fact, there are still very few who understand the content, let alone apply this law from law enforcers alone. Domestic violence can be triggered by many factors, including economic factors, low education, jealousy and can also result in the presence of one person old from both sides, who take part in a household. From education factor can be caused by lack of knowledge from both side how to balance and overcoming unsuitable traits between them, maybe in a household there is husband who have arrogant nature and tend to win by themselves because of lack of knowledge. Legal basis of handling violence in the household, among others, is article 294 paragraph (I) of the Penal Code (KUHP) that threatens a person who commits an obscene act with his or her immature son, stepchild or retrieve, his or her pets and so on with criminal penalty for seven years . Article 340 of the Criminal Code on premeditated murder, Articles 341 and 342 on the murder of women against their babies, Article 356 on family persecution and so on. In addition to the Criminal Code (Penal Code), there are also laws regulating the Elimination of Domestic Violence. Keywords: Domestic Violence